2002
DOI: 10.1021/jp013171e
|View full text |Cite
|
Sign up to set email alerts
|

Dual Fluorescence and Excited-State Structural Relaxations in Donor−Acceptor Stilbenes

Abstract: The time-resolved fluorescence behavior of two derivatives of 4-(dimethylamino)-4′-cyanostilbene (DCS) bearing a more voluminous (JCS) and less voluminous anilino group (ACS) was investigated in ethanol by reconstructing the emission spectra using picosecond time-resolved single-photon-counting technique. For JCS, these spectra exhibit a temporary isosbestic point, a clear indication of level dynamics between two emitting excited singlet states (LE and CT). Kinetic evaluation yielded a precursor-successor rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 49 publications
6
68
1
Order By: Relevance
“…For 6, indeed a decrease in k nr with increasing solvent polarity is found. This is in agreement with what was found for JCS, [83,84] for which the yield of the nonradiative decay also decreases with increasing solvent polarity.…”
Section: Polarity Increases From Left To Right; Diethyl Ether (A) Etsupporting
confidence: 92%
See 1 more Smart Citation
“…For 6, indeed a decrease in k nr with increasing solvent polarity is found. This is in agreement with what was found for JCS, [83,84] for which the yield of the nonradiative decay also decreases with increasing solvent polarity.…”
Section: Polarity Increases From Left To Right; Diethyl Ether (A) Etsupporting
confidence: 92%
“…Both E* and A* are highly polar, with an increased dipole moment for A*; P* has weak or nonpolar properties. [83] Therefore, an increase in the solvent polarity stabilizes E* and A*, and to a much lesser extent P*. As a result, the nonradiative decay, which is governed by the access to P*, becomes less important.…”
Section: Polarity Increases From Left To Right; Diethyl Ether (A) Etmentioning
confidence: 99%
“…Compounds in which rotation of molecular moieties about single and double bonds is possible in nonpolar solvents generally have low fluorescence quantum yield Φ fl [14], and quenching is due to adiabatic transitions to a low-lying non-fluorescent "phantom" state "twisted" about the double bond [13,14]. For model compounds in which internal rotation about the double bond is chemically ruled out [14,15] and for "rigid" coumarin dyes [16-18], a high fluorescence quantum yield has been observed (Φ fl ≥ 0.5) in nonpolar solvents. Φ fl also markedly increases as the viscosity of the nonpolar medium increases, as a result of hindrance of the internal…”
mentioning
confidence: 99%
“…The photophysical properties of organic compounds with electron-donor and electron-acceptor substituents have been widely studied recently [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. They are of interest in connection with their possible application as organic light-emitting diodes in color graphical displays [6], fluorescent labels and visualizing agents in biological systems [7,8], and also owing to their nonlinear optical properties [9, 10] (high quadratic polarizability β).…”
mentioning
confidence: 99%
“…It has been shown that N,N-dimethylamino-p-cyano stilbene (DCS) and its derivatives exhibits dual fluorescence due to the existence of LE and CT excited states [33][34][35][36][37][38][39][40][41][42]. Such systems show large solvatochromic, red-shifted fluorescence with high fluorescence quantum yield (Φ f ).…”
Section: Excited State Charge Transfer Processes In Diphenylpolyenesmentioning
confidence: 99%